Meaning and words in the conference interpreter’s mind – effects of interpreter training and experience in a semantic priming study - Chmiel, Agnieszka (Benjamins, 2018)
The aim of the study was to examine how interpreter training and experience influence word recognition and cross-linguistic connections in the bilingual mental lexicon. Sixty-eight professional interpreters, interpreter trainees (tested at the beginning and end of their training) and bilingual controls were asked to complete a semantic priming study. Priming is a psycholinguistic research method used to examine connections between words and languages in the mind. Data analysis conducted by means of linear mixed models revealed that advanced trainees recognised words faster than beginners, but were not outperformed by professionals. A priming effect was found only in the L1-L2 direction, suggesting similar asymmetries between languages irrespective of the interpreting experience. It is the first study to adopt a priming paradigm and a longitudinal design to examine the interpreters’ mental lexicon. The study shows that word recognition is faster due to interpreter training, but is not modulated further by interpreting experience.
Keywords: Interpreting Studies; priming; interpreting experience; interpreter training; mental lexicon; word recognition